Associated Factors of Red Blood Cell Alloimmunization among Solid Cancer Patients in Teaching Hospital in Malaysia (Bangladesh Journal of Medical Science, 2023)
Background: Alloimmunization is a known complication following repeated red blood cell transfusions. However, the associated factors of RBC alloimmunization are different among blood recipient groups. This study aimed to determine the associated factors of red blood cell alloimmunization among solid cancer patients in Hospital USM.Material and Methods: This cross-sectional study involved 322 adult solid cancer patients screened for red cell alloantibodies in our centre from October 2016 until February 2019. The clinical and transfusion data were obtained from the patient’s medical record and laboratory information system (My Transfusi). The multiple logistic regression was used for analysis of potential associated factors of red blood cells alloimmunization, and p-value of less than 0.050 was considered statistically significant.Results: The patient’s mean age was 52.0 years old, with the majority were Malays (91.0%) and females (61.2%). The most common cancers were breast (32.3%) followed by gastrointestinal (16.8%) and head and neck (14.3%). The presence of metastases (adjusted OR=13.53, p=0.017), numbers of packed red cell transfusions (adjusted OR=1.12, p= 0.015), and blood group A (adjusted OR=7.45, p=0.003) were the associated factors of alloimmunization.Conclusions: Solid cancer patients with metastases, received a higher number of packed red cell transfusions, and blood group A were at higher risk for alloimmunization. Strategies to provide phenotype RBC should focus on this type of patient to prevent red blood cells alloimmunization in solid cancer patients.Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 379-384